ANALYZING THE FINANCIAL FEASIBILITY OF PT. CROWN TEKNOLOGI INDONESIA'S MEDICAL GLOVE PRODUCTION EXPANSION - Dewi, Rahma Ilahi Sari; Afgani, Kurnia Fajar (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
This feasibility study examines the expansion of PT. Crown Teknologi Indonesia (CTI) into the production of medical gloves, a market segment showing significant growth due to increased global awareness of infection control and the rising demand for healthcare products. The study evaluates the financial viability, market potential, and associated risks of establishing a new production facility in Padang, Indonesia, scheduled to begin operations in 2028. The market analysis reveals strong demand for medical gloves in the Asia-Pacific region, projected to grow at a compound annual growth rate (CAGR) of 11.1% from 2022 to 2029, with Indonesia's market expected to expand from USD 40.951 million in 2022 to USD 70.100 million by 2029. CTI’s new facility will produce high-quality nitrile gloves, crucial for maintaining hygiene standards in healthcare settings. Financial projections indicate the project's attractiveness, with a net present value (NPV) of IDR 461.56 billion, an internal rate of return (IRR) of 25.30%, profitability index of 25.30%, a payback period of 7.15 years, and discounted payback period of 8.83 years, all of which affirm the project’s profitability and alignment with CTI's strategic goals. The study concludes that this expansion is not only financially feasible but also strategically beneficial, positioning CTI to capitalize on growing market opportunities while contributing to the enhancement of Indonesia's healthcare infrastructure.